Odpowiedzi

2010-02-05T15:09:41+01:00
A) 2(a+b)=2a+2b
b) 3(x+2y -6)=3x+6y-18
c) -2(x+4-y+z)=-2x-8+2y-2z
d) x(2y-54)=2xy-54x
e) x(2x²-x+7)=3x^3-x^2=7x
f) a(b+a -ab) =ab+a^2-a^2b
108 4 108
2010-02-05T15:09:48+01:00
A) 2(a+b)= 2a+2b
b) 3(x+2y -6)= 3x+6y-18
c) -2(x+4-y+z)=-2x-8+2y-2z
d) x(2y-54)=2xy-54x
e) x(2x²-x+7)=2x³-x²+7x
f) a(b+a -ab) =ab+a²-a²b
41 3 41
Najlepsza Odpowiedź!
2010-02-05T15:09:51+01:00
A) 2(a+b)= 2a + 2b
b) 3(x+2y -6)= 3x+6y-18
c) -2(x+4-y+z)= -2x - 8+2y-2z
d) x(2y-54)= 2xy -54x
e) x(2x²-x+7)= 2x³-x²+7x
f) a(b+a -ab) =ab + a²-a²b
134 4 134